L’existence et le nom du Front populaire comme enjeux d’interprétation et d’appropriation (1936-1938) - François Godicheau (Mélanges de la Casa de Velázquez)
During the Spanish Civil War, the Popular Front remained a successful formula, the «trade mark» of a successful electoral mobilisation, an emblem of the working classes in whose name the parties of the left campaigned prior to 18 July 1936. However, it was trivialised in the early months of the war and was superseded by the insistent calls for «unity». The PCE found the latter effective as a stick with which to beat those they presented as enemies, while the  Popular Front fell into disuse and was abandoned, to the intense disgust of Palmiro Togliatti. Nonetheless, in the summer of 1937 the expression was revived as a battleaxe when it seemed that unity might be used as a weapon against the communists. When it reappeared in the spring of 1938, the formula demonstrated all its worth as a tool of political control in the hands of the «Popular Front» government of national unity.